Distributions of Extracellular Peptidases Across Prokaryotic Genomes Reflect Phylogeny and Habitat - Nguyen, Trang T. H.; Myrold, David D.; Mueller, Ryan S. (Frontiers in Microbiology, 2019)
Proteinaceous compounds are abundant forms of organic nitrogen in soil and aquatic ecosystems, and the rate of protein depolymerization, which is accomplished by a diverse range of microbial secreted peptidases, often limits nitrogen turnover in the environment. To determine if the distribution of secreted peptidases reflects the ecological and evolutionary histories of different taxa, we analyzed their distribution across prokaryotic lineages. Peptidase gene sequences of 147 archaeal and 2 191 bacterial genomes from the MEROPS database were screened for secretion signals, resulting in 55 072 secreted peptidases belonging to 148 peptidase families. These data, along with their corresponding 16S rRNA sequences, were used in our analysis. Overall, Bacteria had a much wider collection of secreted peptidases, higher average numbers of secreted peptidases per genome, and more unique peptidase families than Archaea. We found that the distribution of secreted peptidases corresponded to phylogenetic relationships among Bacteria and Archaea and often segregated according to microbial lifestyles, suggesting that the secreted peptidase complements of microbial taxa are optimized for the environmental microhabitats they occupy. Our analyses provide the groundwork for examining the specific functional role of families of secreted peptidases in relationship to the organisms and the corresponding environments in which they function.